penerapan sistem manajemen keselamatan dan kesehatan kerja di PLN ULP Rantepao Toraja Utara: Implementation Of Occupational Health and Safety Management System at PLN ULP Rantepao, North Toraja. - rumae, Adel (Jurnal Health Sains, 2025)
ADELFINA RUMAE, 2025. Implementation Of Occupational Health and Safety Management System at PLN ULP Rantepao, North Toraja. (Supervised by Apdiyani Toalu and Muhammad Rifai) Occupational Health and Safety (OHS) is an essential aspect in the workplace, especially in the electricity sector, which is known for its high risks. The application of the Occupational Health and Safety Management System (OHSMS) is therefore crucial to prevent workplace accidents and to create a safe and healthy work environment. PLN ULP Rantepao, North Toraja, is one of the operational units under the Sulawesi South, Southeast, and West Region Main Unit (UIW Sulselbar). This research aims to comprehensively describe the implementation of the Occupational Health and Safety Management System (OHSMS) at PLN ULP Rantepao, North Toraja. The research uses a descriptive qualitative approach, referring to the five main elements of OHSMS according to Government Regulation No. 50 of 2012: OHS Policy Determination, OHS Planning, OHS Plan Implementation, OHS Performance Monitoring and Evaluation, as well as OHSMS Review and Improvement. Data were collected through interviews, direct field observation, and supporting documentation. The results show that the OHS policy is established by the Main Unit (UIW Sulselbar), while PLN ULP Rantepao, North Toraja is responsible for technical implementation in the field. OHS planning is carried out collaboratively, involving all divisions including field technicians. OHS implementation has been running well, as indicated by the provision of PPE, work permits, and regular safety briefings before starting work. However, challenges remain, such as the inconsistency of some workers in using PPE. Monitoring and evaluation are conducted systematically through regular inspections and the PLN Inspekta application. OHSMS review and improvement are carried out based on employee input, evaluation results, and SOP adjustments to ensure the sustainability and effectiveness of the system. Overall, the implementation of OHSMS at PLN ULP Rantepao, North Toraja has been adequate. Nevertheless, there is still a need to improve employees’ awareness and discipline regarding the OHS culture. It is recommended that training, outreach, and supervision of OHS implementation continue to be enhanced to achieve a safer and more sustainable work culture. Keywords: OHSMS, PLN, Safety Management, Performance Evaluation.